A guide to effective management of germplasm collections - Engels, J.M.M.; Visser, L. (2003)
The initiative to bring experts together to discuss the consequences of changes in the roles and responsibilities of genebanks led to this publication. It is hopes that the ideas put forward lead to more critical balanced and creative approach towards genebank operations on the part of genebank curators worldwide. It is also hoped that decisions concerning concepts and strategies that have been or will be made at the institutional and national level on the conservation and use of plant genetic resources will be made easier by this publication. Genebank are encouraged to share their experiences through all means of communication. The reader is kindly invited to provide IPGRI with any comments or suggestions on the current text that would contribute to more effective and efficient conservation and thereby assist in the generation of a solid knowledge base for genebank management.